Pengaruh Leverage, Pertumbuhan Penjualan, Struktur Modal, Dan Arus Kas Bebas Terhadap Manajemen Laba - Nasution, Ade Meilany; Purnasari, Nina; Sianturi, Yuni Dameriani; Herliani, Rini (Universitas Gorontalo, 2024)
This study aims to analyze the effect of leverage, sales growth, capital structure and free cash flow on earnings management in food and beverage sub-sector manufacturing companies listed on the IDX in 2019-2022. This study used 52 samples which were processed using spss. The test results explain that leverage, sales growth, free cash flow and capital structure simultaneously affect earnings management in manufacturing companies listed on the IDX for the 2019-2022 period. leverage and capital structure have a significant effect on earnings management in manufacturing companies listed on the IDX for the 2019-2022 period. While sales growth and free cash flow have no effect on earnings management in manufacturing companies listed on the IDX for the 2019-2022 period.